Research on Technical Architecture on the SPICE of Open Source VDI - Yirong Shi; Dezhi Gong (Dianxin kexue)
The features and scenarios and agreement of VDI were stated,performance of agreement base testing,and the functional architecture and programming architecture base desktop and interface calls and data channel of the SPICE were analyzed.The important point of technology and the prospect of SPICE were proposed.